The Pathogenesis of AIDS: Classical and Alternative Views - Dalgleish, A. G. (J R Coll Physicians Lond, 1992)
As HIV readily kills CD4 cells in vitro it has been widely assumed that this would account for the declining CD4 counts in vivo. A growing number of reports suggest that the pathogenesis of AIDS is considerably more complex than had been thought. A number of indirect mechanisms for CD4 cell death have been proposed. In this review of alternative theories which could explain the features of AIDS, autoreacivitiy and genetic restriction to the development of disease are considered the most important. In addition it is suggested that if HIV is able to mimic MHC antigens on the surface of antigen presenting cells then this could stimulate 'allo reactive' T lymphocytes, which would explain the marked similarity of HIV infection to chronic graft versus host disease.